1980
DOI: 10.1159/000145319
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal deficits in mice following phenobarbital exposure during various periods in fetal development

Abstract: Four groups of pregnant mice were fed milled food containing 3 g/kg phenobarbital, acid, form, and water as their only nutritional source during various periods during pregnancy (days 9–18, 9–13, 13–16 or 16–18). Control females received milled food and water. The brains of control and phenobarbital-treated male offspring were removed at age 50 days, fixed, cut and stained with HE. Matching sagittal sections were selected for the study of the cerebellar Purkinje cells and the hippocampal pyramidal cells. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Related to effects on brain development, exposure to phenobarbital during gestation led to a significant decrease in cell proliferation in an area of the hypothalamus (the medial preoptic area) of female Sabra mice [169], decreased number of hippocampal pyramidal cells [170–173], and decreased number of cerebellar Purkinje and granule cells [174]. In light of data showing a similar effect after phenytoin, it has been suggested that early life exposure to AEDs can cause increased programmed cell death, a potentially devastating effect for the developing brain (discussed further below).…”
Section: Animal (Rodent) In Utero Aed Exposurementioning
confidence: 99%
“…Related to effects on brain development, exposure to phenobarbital during gestation led to a significant decrease in cell proliferation in an area of the hypothalamus (the medial preoptic area) of female Sabra mice [169], decreased number of hippocampal pyramidal cells [170–173], and decreased number of cerebellar Purkinje and granule cells [174]. In light of data showing a similar effect after phenytoin, it has been suggested that early life exposure to AEDs can cause increased programmed cell death, a potentially devastating effect for the developing brain (discussed further below).…”
Section: Animal (Rodent) In Utero Aed Exposurementioning
confidence: 99%
“…Indeed, prenatal PhB treatment, which affected the MPOA in the present studies, also affected sex hormones and reproductive functions [Gupta et al, 1980a, b]. Prenatal and neonatal exposure to PhB affected neuronal number and various regions of the brain Bergman et al, 1980;. The surviving cells exhibited changes in the dendritic spines [Yanai and Iser, 1981] as well as ultrastructural changes [Fishman et al, 1981].…”
Section: Discussionmentioning
confidence: 79%
“…The sexual function was also impaired in both sexes. It is known that the hypothalamus develops prenatally in the rodent [Crep, 1974;Ifft, 1972;Shimada and Nakamura, 1973] and that administration of PhB to pregnant ani mals caused long-lasting neuronal deficits in prenatally forming neurons in the cerebel lum and hippocampus [Bergman et al, 1980;Yanai et al, 1979]. The present experiment was designed to investigate in mice whether neuronal number and rate of proliferation of the MPOA cells are sexually dimorphic in the MPOA, and to study the effect of PhB, administered prenatally on these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice that express a stabilized form of β‐catenin in neuronal progenitor cells develop grossly enlarged brains with a concomitant increase in cerebral cortical surface (Chenn & Walsh, 2003). Treatment of rodents with phenobarbital revealed an interference with cellular proliferation, resulting in decreased brain weight and neuronal number (Yanai et al., 1979, 1981; Bergman et al., 1980).…”
Section: Main Events Of the Cns Development And Their Impairment By Aedsmentioning
confidence: 99%